Digital Parenting Meningkatkan Perkembangan Anak Yang Berkualitas - Nurselvi Fajria; Abie Syifa Mahendra; Martiana Fita Setiani; Faiz Roziqi; Muslikah Muslikah; Ashari Mahfud (Pusat Riset dan Inovasi Nasional, 2025)
Digital technology has had a profound impact on contemporary parenting patterns, particularly among children born in the digital era. This study aims to examine the influence of digital parenting on enhancing early childhood development by employing a comprehensive literature review.It synthesizes extant research findings to elucidate the relationship between digital parenting and child development.The findings indicate that effective digital parenting practices, such as content monitoring, time restriction, and digital ethics education, can contribute to the development of quality children. Additionally, the study underscores the significance of open communication between parents and children in mitigating the potential adverse impacts of digital technology.This research offers novel insights into the pivotal role of parents in guiding children in the digital age and puts forth practical strategies that can be integrated into daily parenting practices.